Worship in the Mosque during the Pandemic: A Study of Islamic Law: Ibadah di Masjid pada Masa Pandemi: Telaah Hukum Islam - Absor, Ulil; Hafsah , Hafsah; Siregar, Ramadhan Syahmedi (Universitas Muhammadiyah Sidoarjo, 2023)
The Covid-19 pandemic has affected almost every aspect of Indonesian life, including religious aspects such as the ban on congregational prayers in mosques. The measures taken by the government are certainly controversial among the public. The purpose of this study was to find out the practice of holding congregational prayers during the Covid-19 pandemic in Medan City based on the contemporary Ulama Ijtihad method and Islamic law. The method used in this study is a qualitative research method. The results of the study show that congregations in Medan City can still perform congregational prayer at the mosque, but by implementing strict health protocols such as applying a distance of at least 1 metre for prayer, mandatory wearing of masks, using their prayer mats, performing ablution (wudu) at home respectively, congregations are not allowed to gather at the same time as well as not allowed to bring such children to the mosque.Highlights: Congregational prayers are allowed, with strict health protocols. Measures include maintaining 1-meter distance, wearing masks, and using personal prayer mats. Other precautions involve performing ablution at home, staggering arrival times, and prohibiting children in mosques. Keywords: Congregational Prayer, Ijtihad method, contemporary ulama, Covid-19